Character Education for Ethical Leadership in Indonesian Senior High Schools - Wangi, Eneng Nurlaili; Rosiana, Dewi; Sartika, Dewi; Suhana, Suhana; Lutfiani, Siti Mutya; Charles, Suri (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
This study investigates the internalization of two key character values, respect and responsibility, among senior high school students in Bandung, Indonesia. It evaluates how these values are fostered through local character-education initiatives such as the Bandung Masagi program and examines their implications for developing integrity-based leadership in adolescents. Using a quantitative descriptive design, the research involved 103 students who completed the Respect and Responsibility School Culture Survey (SCCP-II). The findings reveal that all students demonstrated high levels of respect, indicating strong internalization of this value. Responsibility, however, showed greater variability, with 52% of students classified as high, 46% moderate, and 2% low. Bullying behaviors persisted at moderate levels, with 10% of students reporting high exposure or involvement. These results highlight a discrepancy between curricular intent and behavioral outcomes, raising questions about the depth of value internalization and the role of pedagogical implementation. This research provides a culturally contextualized framework that links respect, responsibility, and bullying prevention to the development of adolescent leadership character. The study provides practical recommendations for educators and policymakers, including structured character-education curricula, enhanced teacher role modeling, and participatory strategies that strengthen the internalization of values. By integrating these insights, Indonesian schools can cultivate future leaders more effectively with empathy, accountability, and resilience.